IDENTIFICATION OF ARABIC LEARNING STYLES FOR STUDENTS ON CLASS XI SCIENCE AT AL-FALAH SENIOR HIGH SCHOOL JAMBI - Annisa Padila; K.A Rahman; Mar’atun Sholiha (International Journal of Islamic Education, Research and Multiculturalism (IJIERM), 2020)
Abstract: This study aims to determine the learning style tendencies of XI Science class students at Al-Falah Islamic High School Jambi City. This research method is a survey with a quantitative approach. The variables in this study are learning styles which include visual, auditory and kinesthetic. The population in this study were all students of class XI science in Islamic Senor High School Islam Al-Falah Jambi City. The data collection technique uses a closed questionnaire through the application Google Form. The analysis technique used is descriptive statistics. The results showed that every student of class XI IPA Islamic Senor High School Al-Falah Jambi City has a tendency to one of the visual, auditory or kinesthetic learning styles. The majority of students have a tendency to visual learning styles with details of 88 students, as many as 43 students or 48.9% have a tendency to a visual learning style characterized by reading, while 25 students or 28.4% have a tendency to an auditory learning style characterized by listening and learning. 20 students or 22.7% of students have a tendency to the kinesthetic learning style which is characterized by having creative creativity.